Treatment of head and neck cancer in the elderly. (21st September 2016) - Hartmann, Stefan; Grandis, Jennifer R.
ABSTRACT: Introduction : Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide and the majority of patients present with advanced stage disease. Chemotherapy is an important component of head and neck cancer treatment regimens and has shown beneficial effects in locally advanced and recurrent/metastatic stages of disease. Approximately 25% of HNSCC patients are aged 70 and older, often associated with co-morbid medical conditions. Most clinical trials exclude patients of advanced chronological age such that valid information about the efficacy and safety of drugs and treatment regimens in elderly patients is not available. Areas covered : Surgery, radiotherapy and particularly chemotherapy with the six FDA-approved chemotherapeutic agents for head and neck cancer treatment are discussed with a focus on age, performance status, comorbidities. New targeted therapies and the field of immune checkpoint inhibitors are evaluated in the context of elderly populations. Expert opinion : Surgery, radiotherapy and administration of cytotoxic chemotherapeutic agents are largely safe and effective in elderly patients. Targeted therapies are mostly well tolerated. Clinical studies should be designed to include elderly patients (>70 years). Immune checkpoint inhibitor therapies may exert age-related effects, since substantial functional changes in T cell responses increase during the aging process.